Goosebumps. Attack of the jack-o'-lanterns [videorecording (DVD)] - Fruet, William, 1933-; Oliver, Ron; Stine, R. L. (Goosebumps., 2009)
Three episodes from the television series Goosebumps originally produced in 1996.